Inovasi Melalui Desain: Model R&D Yang Diperbarui Dengan Metode Perancangan Desain Grafis Pada Konteks Pengembangan Buku Ajar Yang Kreatif: Innovation Through Design: An Updated R&D Model with Graphic Design Design Methods in the Context of Creative Textbook Development - Arifin, Irfan; A Rauf , Bakhrani; Ahmad, Arifin (Efektor, 2023)
This research aims to update the research and development (R&D) model by integrating graphic design design methods to improve quality and creativity in textbook development. By modifying the Dick, Carey, & Carey development model and applying the design thinking method approach. The research method focuses on creating innovation through three related stages, namely Needs Identification and Preliminary Research, Conceptual Framework Analysis, and Prototype Development. The research resulted in a modification of the development model that is more responsive and adaptive to contemporary needs in the world of education. With 4 steps the development stages become simpler. Called the Ir-FAN development model: 1) Identification & Research stages of problem identification with in-depth research; 2) Design phase, is the planning and design stage; 3) Reflection activities, implementation and evaluation stages; and 4) Effective value that can be achieved, the final stage is optimization and development.